PENGEMBANGAN PENUNTUN PRAKTIKUM TIPE DISCOVERY PADA MATERI LARUTAN ASAM BASA DI SMA NEGERI UNGGUL SIGLI - Zakiah, Zakiah; Maisura, Maisura; Makawiyah, Makawiyah; Zahara, Rina (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2022)
This research is a research development practicum guide in the field of chemistry education. The aims of this research are (1) to obtain a practicum guide based on the Discovery type syntax, (2) the significant difference in the improvement of learning outcomes that are learned using the existing practicum guides at school with the Discovery type practicum guides, (3) the effectiveness of the learning process taught by using the Discovery type practicum guide. using the Discovery type practicum guide. The stages in this research are (1) Syntax analysis of the Discovery learning model to determine the components of the chemical practicum guide according to the Discovery type, (2) Compile and develop a chemical practicum guide on acid-base solution materials according to the Discovery type syntax, (3) Standardization or feasibility test of practicum guides for teacher validators, (4) Implementation of practicum guides for class XI students of SMA Negeri Unggul Sigli, (5) Analyzing the effectiveness of the Discovery type practicum guide in learning Acid-Base Solutions that have been tested. The results of the feasibility test for the Discovery type practicum guide 3.41 and the practicum guide at school 2.31. While the effectiveness of the use of the Discovery type practicum guide and the practicum guide commonly used in schools, judging by student learning outcomes, it is known that the experimental class I which uses the Discovery type practicum guide is an average of 86.00 with an increase in learning outcomes of 71.4% while the experimental class II which uses a practicum guide in the LKS an average of 61.75 with an increase in learning outcomes of 58.8%. So it can be concluded that the Discovery type practicum guide and the practicum guide being studied are feasible to be used as practicum guides in schools, with increased learning outcomes using the Discovery type practicum guide being higher in value than the existing practicum guides in the lectures.Keywords: Development of Practicum Guide, Type of Discovery.